Water productivity and yield characteristics of transplanted rice in puddled soil under drip tape irrigation - Nabipour, Ramtin; Yazdani, Mohammad Reza; Mirzaei, Farhad; Ebrahimian, Hamed; Alipour Mobaraki, Fatemeh (Agricultural water management, 2024)
Lowland rice flooding, while consuming considerable water, has adverse environmental effects, including releasing methane into the atmosphere, aggravating climate change. Several drawbacks can be attributed to water-saving alternatives, such as aerobic rice, whereas rice drip irrigation techniques have been evaluated primarily under aerobic conditions. This study investigated drip tape irrigation technique with different lateral spacings for transplanted rice in puddled paddy soil at the Rice Research Institute of Iran in Rasht over two years (2020 and 2021), compared to intermittent irrigation. In twelve isolated concrete basins, three treatments with lateral spacings of 40 (T40), 60 (T60), and 80 cm (T80), were compared with a fixed five-day period intermittent irrigation (INT). In 2020 and 2021, the INT treatment produced the highest grain yield (3814 and 4758 kg ha−1, respectively) and among drip tape treatments, T40 demonstrated the highest grain yield (3613 and 4020 kg ha−1, respectively), comparable with INT’s yield but with the highest sterile spikelets ratio. In contrast, T80 resulted in the lowest grain weight (2892 and 3653 kg ha−1, respectively) and yield characteristics values, while producing the highest weeds population. Drip tape irrigation significantly reduced water application by 27% and 36% in 2020 and 2021, respectively and T40 achieved the highest water productivity, at 0.68 kg m−3. The economic water productivity estimation of drip tape irrigation can range from 0.11 to 0.51 US$ m−3 in various scenarios, while that of intermittent irrigation remains at 0.25 US$ m−3. •Drip tape irrigation of transplanted rice compared to intermittent irrigation (INT).•Drip irrigation saved water by up to 36% compared to INT.•WP ranged between 0.44 and 0.68 kg m−3, an increase of up to 22% compared to INT.•40 cm lateral spacing is the most yielding and profiting drip irrigation formation.